China's evolving managed float: An exploration of the roles of the fix and broad dollar movements in explaining daily exchange rate changes - John Clark (Federal Reserve Bank of New York, 2017)
We investigate the drivers of daily changes in the exchange value of the Chinese currency (CNY) since early 2016, when a new regime was introduced for setting the fix - the midpoint of the CNY's daily trading range against the U.S. dollar. Daily changes in the fix, which is announced just prior to the onset of onshore trading, are shown to be highly predictable and very responsive to the change in the CNY/USD rate during the previous day's onshore trading session and to changes in dollar cross rates. While highly predictable, the fix is shown to have uneven predictive power for the subsequent evolution of the currency's exchange value. Daily changes in the closing value of the exchange rate have centered on the changes implied by the fix to a much greater extent in months with higher intervention intensity, but less over the course of 2017, as intervention has waned. We document ways in which the short-run behavior of the CNY/USD exchange rate has evolved to more closely resemble behavior generally observed in freely floating currencies, even as the CNY continues to exhibit unusually low daily volatility. On days of broad dollar strengthening, the CNY is found to depreciate against the dollar but appreciate against the CFETS index, the authorities' main reference basket; the CNY now typically appreciates less than half as much as previously, when the currency was being managed primarily against the dollar.
Keywords: F3; F31; F33; G15; O16; 330; Chinese currency; Chinese yuan; CNY; exchange rate regime; currency policy; flexible exchange rate; intervention; financial development